Ambivalence on East and West Discourse As Seen in Dwi Cipta’s Short Story Tanah Merah - firdiansyah firdiansyah (English Language, Linguistics, Literature, And Education Journal, 2019)
The colonization of Westen countries towards Eastern countries bring the identification of themselves as civilized countries and tend to identify colonized countries as uncivilized countries. However, all the efforts of identification that they have done only bring contradiction toward their identity as civilized nation. Many actions that have been done toward people in Indonesia,especially in Digul, shows that they are not better than colonized nation (Eastern country). It can be analyzed more in Dwi Cipta’s work Tanah Merah by using Homi.K Bhabha’s theory about ambiguity and polisemic discourse. The research will try to analyze the split identity of Western nation (colonizer) and Eastern nation (colonized). Having conducted the research, the writer prove that there is split identity of Western nation toward Eastern nation. It means all efforts to identify Westen nation as civilized nation only bring the opposite condition or identity of themselves toward Eastern nation.